Effect of the Number of PZT Coatings on the Crystal Structure and Piezoelectric Properties in PZT-CNT Nanocomposites - Kang, Sin Wook; Cho, Sam Yeon; Bu, Sang Don; Han, Jin Kyu; Lee, Gyoung-Ja; Lee, Min-Ku (Journal of the Korean Physical Society, 2018)
In this study, a nanocomposite was successfully fabricated by mixing Pb(Zr,Ti)O3 (PZT) prepared by using the sol-gel method and functionalized multi-walled carbon nanotubes (MWCNTs). During this process, the effect of the change in the molar concentration of PZT on the crystallinity and the piezoelectric properties of the PZT in the nanocomposite was investigated. As the number of PZT coatings was increased from one to three, PZT was confirmed as having completely covered the MWCNT nanocomposite. Also, the tetragonality of PZT in the crystal structure was confirmed to have increased with increasing number of PZT coatings. Such an increase in crystallinity was followed by an increase in the ferroelectricity of the nanocomposite. A nano-generator was fabricated by using the nanocomposite fabricated as described above, and the characteristics of the nanogenerator were confirmed to have been improved with increasing number of coatings.